Surgical outcome of strabismus - Shrestha, Sabina; Manoranjan, Aparajita; Shrestha, Sushan (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Strabismus is encountered daily by paediatric ophthalmologists and orthoptists in their practice.Strabismus and amblyopia affect 5% of the population. The aim of the study was to determine the surgicaloutcome of strabismus. Methods: It was a prospective study conducted at Nepal Eye Hospital from 2010 to 2011 with the samplesize of 40. Patients undergoing strabismus surgery either for esotropia or exotropia were included in the study.Detailed preoperative and postoperative orthoptic evaluation of all the patients was done apart from the anteriorand posterior segment examination and the surgical outcome was assessed. Results: Forty patients of which 52.5% males and 47.5% females with mean age of 21.025 years underwentstrabismus surgery. Manifest divergent squint was present in 61%, manifest convergent squint in 38% andintermittent squint in 5% of patients. 87.5% underwent 2 muscle surgery, 10% underwent 3 muscle surgeryand 2.5% underwent single muscle surgery. Postoperative deviation for near was 0 ???? in 10%, 2-8 ???? in 37.5%and 10-15???? in 27.5%. Similarly, postoperative deviation for distance was 0???? in 22%, 2-8???? in 27% and 10-15????in 22%. Binocular single vision was present in 50% patients preoperatively and 53% patients postoperatively. Conclusion: Though cosmesis has been improved in most of the patients after strabismus surgery, binocularsingle vision and stereopsis improved in very minimal percentage of patients as the surgery was done after theage of visual maturation in most of the cases. This accentuates the need for strabismus surgery within the yearsof cortical plasticity doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12921